KECACATAN AIR MINUM DALAM KEMASAN GELAS 240 ml MENGGUNAKAN P-CHART, DIAGRAM PARETO DAN DIAGRAM ISHIKAWA DI PT. MAAN GHODAQO SHIDDIQ LESTARI (Tembelang, Jombang, Jawa Timur) - , RR. LINGGAWATI H L ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Maan Ghodaqo Shiddiq Lestari is the one company that produce drinking water in Tembelang, Jombang, East Java. This company using artesian water as raw material. Drinking water production process through several stages of filtration and disinfection process to produce a quality product. Quality product is very important to be able to survive in the competition. Not only the main product but also the packaging of the product must be quality. Quality is a crucial factor in the success of a product to penetrate the market. Quality products will have great competitiveness and a high level of acceptance. There are 3 quality in the drinking water, there are quality of raw materials, finished product quality and packaging quality. Required the application of Pareto diagram to determine the criteria for disability and which disability criteria that most often occurs so can using ishikawa diagram to obtain corrective actions that can be done. The calculation is performed by summing all defective products from each company's predetermined criteria then create a Pareto diagram and analyze the causes of the most common defects using ishikawa diagram. Based on calculations, it is known that the number of product defects that occur in the PT. Maan Ghodaqo Siddiq Bieber during the last 3 months are June, July and August amounted to 6264 pieces. Disability is comprised of isi kurang 121 pieces, lid tidak tepat 149 pieces, lid kotor 0 pieces, cup bocor 1584 pieces, cup kempes 0 pieces, expired tidak jelas 0 pieces, cup dobel 0 pieces, cup kotor 55 pieces dan cup pesok 1187 pieces. The highest disability criteria is cup bocor. Disability occurs by machine, human, material, method and environment factors.